Broiler Responses to Dietary Fibre Sources at Different Ages: Effects on Growth Performance, Nutrient Digestibility, Blood Parameters and Intestinal Morphology - Ali Asghar Kardel; Mohammad Kazemifard; Mansour Rezaei; Asadollah Teimouri Yansari (Veterinary Medicine and Science)
ABSTRACT Background Previous studies investigated the effect of different levels of fibre sources, but little research is available on the effect of a bird's age on the type of fibre source. Objectives The study aimed to determine the effect of rice hulls (RHs) and sugar beet pulp (SBP) on growth performance, nutrient digestibility, blood parameters and intestinal morphology of broilers at different ages. Methods A total of 160 newly hatched Ross 308 male broiler chicks were randomly assigned to 4 dietary groups, each with 4 replicates and 10 chicks per replicate. Dietary treatments included: T1: control diet without any additions at grower and finisher periods; T2: diet containing 3% RH in the grower period and 3% SBP in the finisher period; T3: diet containing 3% SBP in the grower period and 3% RH in the finisher period; and T4: diet containing 1.5% RH and 1.5% SBP in the grower and finisher periods. Average growth performance during this period and nutrient digestibility, blood parameters and ilium morphology were evaluated at Days 24 and 42. Results Feed conversion ratio (FCR) of broilers significantly improved in the T2 group from 11 to 24 days and body weight gain (BWG) in T2 and T4 from 11 to 42 days of age (p < 0.05). At 42 days of age, the greatest dry matter (DM), organic matter (OM) and neutral detergent fibre (NDF) digestibility were observed in the T4 group in comparison to the T3 groups (p < 0.05). The ilium villus height–to–crypt depth (VH/CD) ratio increased at 24 days of age in the T1 and T2 groups (p < 0.05). Conclusions Our study showed that the T2 and T4 groups might enhance broiler growth performance through increasing nutrient digestibility and ilium morphology during Days 11 to 42 days of age.